2022
DOI: 10.3390/fermentation8110607
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Function and In Vitro Gas Production of Diets Influenced by Two Levels of Tannin-Rich Forage

Abstract: The aim of this research was to evaluate the effect of the inclusion of Acacia mearnsii (AM) at different levels of inclusion on ruminal digestion and in vitro gas production. A. mearnsii forage was incorporated in the diet at different levels of 0 (AM0), 20 (AM20), and 40 (AM40) %. In situ degradation of dry matter (DM) and organic matter (OM) showed differences between treatments (P < 0.05), obtaining the highest value of the degradation of soluble fraction (A), insoluble but potentially degradable fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The current research employs an equation model to measure gas production’s kinetics. This model is commonly used for analyzing the patterns and rates of gas production in ruminal fermentation experiments [39] .…”
Section: Methodsmentioning
confidence: 99%
“…The current research employs an equation model to measure gas production’s kinetics. This model is commonly used for analyzing the patterns and rates of gas production in ruminal fermentation experiments [39] .…”
Section: Methodsmentioning
confidence: 99%
“…Maranatha et al (2020) fermented corn cobs and moringa leaf flour using EM4, resulting in dry matter and organic matter digestibility of 67.94 and 66.77%, respectively. Vargas-Ortiz et al (2022) reported that using Acacia mearnsii (AM) in feed yielded a dry matter digestibility of 69.5% and an organic matter digestibility of 66.9%. Those different results are due to different types of substrates and enzymes.…”
Section: The Role Of Mixed Microbes To Improve Dry Matter Digestibili...mentioning
confidence: 99%
“…The role of mixed microbes in tannin degradation Tannins are polyphenolic compounds that bind proteins, inhibit protease enzymes, and form complex proteins that cannot be digested. They limit protein availability and reduce digestibility (Olawoye and Gbadamosi 2017); therefore, tannins content in fish feed should not exceed 3% (Vargas-Ortiz et al 2022).…”
Section: The Role Of Mixed Microbes In Increasing Dissolved Proteinsmentioning
confidence: 99%
“…Ruminant production in tropical and subtropical areas is generally based on pasture grazing with a predominance of grasses [1][2][3][4], characterized by low amounts of protein (<7%), a high proportion of structural carbohydrates (60-80%) [5,6] and low digestibility (<50%) [7]. Characteristics that affect the productivity of animals, in response to the consumption of poor quality forage and the subsequent production of greenhouse gases (GHG) (mainly methane (CH 4 ), carbon dioxide (CO 2 ) and nitrous oxide (N 2 O)), as a result of the metabolism of structural carbohydrates, gases that are later eliminated through burping or flatulence and generate considerable energy losses in the animal (2 to 12%) [8][9][10][11]. Ruminants are responsible for producing approximately 47% of CH 4 , 29% of N 2 O, and 27% of CO 2 of total GHG (14.5%) of anthropogenic origin from livestock activity, so the search for possible solutions is very important [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%